Hubungan antara Sikap Kerja dengan Keluhan Musculoskeletal Disorders pada Pekerja Angkut Barang Toko Grosir Komodo di Denpasar - Dewa Ayu Sri Shita Meliani; Suyasning Hastiko Indonesia; Saktivi Harkitasari (Aesculapius Medical Journal, 2022)
The working activities of carrying load workers in Komodo whole sale shop in Denpasar are considered traditional work posture with repetitive movement and some time do poor work posture. The carrying posture triggers the complaint of Musculosceletal disorders ( MSDs). This study aims to distinguish the correlation between work posture and MSDs. The method of the study was analyzed observational which cross sectional approach. The work posture was measured using REBA (Rapid Entire Body Asessment) and MSDs were measured using Nordic Body Map with Likert Scale. The samples were carried out on 41 workers and the data were analyzed using SPSS 22. The results were showed as follows: there was a significant relationship between work posture and MSDs (r=0.85) The conclusion could be drawn that the relationship between work posture and MSDs was significantly. It could be recommended that the work posture should be ergonomic approach.